Investigation of the Functions of Insect Arginine Vasopressin-like Peptides - Edwardson, Fenwicht; Rogan Tokach; Kim, Donghun; Park, Yoonseong (My University, 2017)
The neuropeptide arginine vasopressin (AVP) is a multifunctional signaling peptide that is highly conserved across eukaryotic animals. In mammals, it primarily acts as an anti-diuretic and a regulator of blood pressure. These traits among others merit the study of the arginine vasopressin-like (AVPL) hormone found in insects (Aikins et al., 2008). We investigated the bioactivity of AVPL in an assay measuring the recovery time after knockout in water, indicating hormonal activity for alert states in the red flour beetle Tribolium castaneum. We found that injections of an AVPL mimetic peptide (AVP1) prolonged the knockout time, implying that the AVPL causes longer suppression of the recovery from water shock.
Citation: Edwardson, F. (2017). Investigation of the Functions of Insect Arginine Vasopressin-like Peptides . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.